2013
DOI: 10.1371/journal.pone.0072344
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endoplasmic Reticulum Stress in Albuminuria Induced Inflammasome Activation in Renal Proximal Tubular Cells

Abstract: Albuminuria contributes to the progression of tubulointerstitial fibrosis. Although it has been demonstrated that ongoing albuminuria leads to tubular injury manifested by the overexpression of numerous proinflammatory cytokines, the mechanism remains largely unknown. In this study, we found that the inflammasome activation which has been recognized as one of the cornerstones of intracellular surveillance system was associated with the severity of albuminuria in the renal biopsies specimens. In vitro, bovine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
72
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 31 publications
5
72
0
1
Order By: Relevance
“…21 In vitro cell studies also support changes taking place in PTC with protein overload. [26][27][28] Finally, a study in Wistar rats using three albumin injections, versus two as in our study, showed no change in the glomerular size selectivity. 29 For the present study, we chose an acute albumin overload model using two albumin injections in normal healthy animals.…”
Section: Discussionsupporting
confidence: 46%
“…21 In vitro cell studies also support changes taking place in PTC with protein overload. [26][27][28] Finally, a study in Wistar rats using three albumin injections, versus two as in our study, showed no change in the glomerular size selectivity. 29 For the present study, we chose an acute albumin overload model using two albumin injections in normal healthy animals.…”
Section: Discussionsupporting
confidence: 46%
“…22) However, the effect of UDCA on diabetic nephropathy has remained largely unknown. In the present study, we provide the verification for the protective actions of UDCA on diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The increased UPR in diabetes reveals the existence of ERS (33), including upregulation of nuclear transcription factors such as PERK. Fang et al reported that ERS appeared to play an important part in albuminuriaprovoked inflammasome activation and elimination of ERS via tauroursodeoxycholic acid (TUDCA), which might represent a novel avenue for attenuating kidney epithelial cell damage caused by albuminuria (34). The UPR is a homeostatic response that allows the cells to cope with stressful conditions associated with increased misfolded or unfolded protein loads; failure of this mechanism is referred to as the ERS response (9).The ERS response has been found to play a key role in a growing number of pathological conditions such as DN (10,34,35), and the ERS response is considered to be a cause of chronic inflammation (36).…”
Section: Discussionmentioning
confidence: 99%